Metformin Protects Against Diabetes-Induced Cognitive Dysfunction by Inhibiting Mitochondrial Fission Protein DRP1 - Hu, Yan; Zhou, Yile; Yang, Yajie; Tang, Haihong; Si, Yuan; Chen, Zhouyi; Shi, Yi; Fang, Hao (Frontiers in Pharmacology, 2022)
Objectives: Diabetes is an independent risk factor for dementia. Mitochondrial dysfunction is a critical player in diabetes and diabetic complications. The present study aimed to investigate the role of mitochondrial dynamic changes in diabetes-associated cognitive impairment. Methods: Cognitive functions were examined by novel object recognition and T-maze tests. Mice hippocampi were collected for electron microscopy and immunofluorescence examination. Neuron cell line HT22 and primary hippocampal neurons were challenged with high glucose in vitro. Mitotracker-Red CM-H2X ROS was used to detect mitochondrial-derived free radicals. Results: Diabetic mice exhibited memory loss and spatial disorientation. Electron microscopy revealed that diabetic mice had larger synaptic gaps, attenuated postsynaptic density and fewer dendritic spines in the hippocampus. More round-shape mitochondria were observed in hippocampal neurons in diabetic mice than those in control mice. In cultured neurons, high glucose induced a high phosphorylated level of dynamin-related protein 1 (DRP1) and increased oxidative stress, resulting in cell apoptosis. Inhibition of mitochondrial fission by Mdivi-1 and metformin significantly decreased oxidative stress and prevented cell apoptosis in cultured cells. Treatment of Mdivi-1 and metformin restored cognitive function in diabetic mice. Conclusion: Metformin restores cognitive function by inhibiting mitochondrial fission, reducing mitochondrial-derived oxidative stress, and mitigating neuron loss in hippocampi of diabetic mice. The protective effects of metformin shed light on the therapeutic strategy of cognitive impairment.